CSF Neurofilament light chain level predicts axonal damage in cerebral vasculitis. Issue 6 (3rd June 2019) - Pawlitzki, Marc; Butryn, Michaela; Kirchner, Florian; Färber, Jacqueline; Beuing, Oliver; Minnerup, Jens; Meuth, Sven G.; Neumann, Jens
Abstract: The rarity of primary angiitis of the central nervous system (PACNS) demands diagnostic and prognostic biomarkers. We retrospectively measured Neurofilament light chain (NFL) concentrations in cerebrospinal fluid in a severely relapsing PACNS patient at multiple time points during the course of the disease. A marked increase in NFL levels preceding the onset of neuro‐axonal damage and arterial‐vessel abnormalities was observed with magnetic resonance imaging as well as with MR‐ and conventional angiography. Thus, marked elevation of NFL in PACNS seems to occur ahead of definitive radiological abnormalities and might serve as a diagnostic biomarker.